148k views
4 votes
2x + 5y = 13
-x + 4y = 13
solve by elimination

User Deses
by
4.8k points

2 Answers

4 votes

Answer:

x = -1 , y = 3

Explanation:

2x+5y = 13

-x+4y = 13

Decide whether to add or subtract the two equations by using Different Add Same Subtract (DASS) or in case below as its SUBTRACT

i apply (SDSS).

We subtract 5y as this is easier equation either positive prioritises or if both positive then easier number becomes priory.

Results to SDSS before substituting Y if 5y etc was subtracted

2x+5y = 13 Subtract -5

2x+5y -5y = 13 -5y

2x= 13 - 5y then Divide by 2

2x / 2 = 13/2 - 5y/2 Show then

x = 13 - 5y / 2 + 4y = 13 Simplify

simplify 13 - 13y / 2 as y = 3

as 13/2 = 6.5 and 2.5 +4 = 6.5

y = 3

Substitute y = 3

13-5y )3) / 2

13-5 (3) / 2

BODMAS Brackets first Multiplying only for y substitute 5y = 5 x 3

-5 (3) = 15

13-15 = -2

-2/2 = -1

x = -1

User Jigar Surana
by
4.5k points
7 votes

Answer:

i think x=-1 and y=3. ....

User Dhiren Basra
by
5.6k points